Peningkatan Model Discovery Learning Dalam Meningkatkan Hasil Belajar Pada Tematik Terpadu Kelas IV SD - Fanygia Safitri; Desyandri Desyandri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aimed to describe the increase of students learning outcome on thematic integrated learning using Discovery Learning. This research was classroom action research with qualitative and quantitative approaches. The participants of this research SDN 21 Bandar Buat. The results showed: 1. Lesson plan assessment in cycle I was 78.12% then increased to 100% in cycle II. Observation on teacher aspect in cycle I was 84,37% and went up to 100% in cycle II while on aspect of students in cycle I was 84,37% the increased to 100% in cycle II. Affective aspect of students, the were 3 student who showed caring, honestly in cycle I. It increased to 5 students in cycle II. Cognitive aspect, in cycle I was 77.14 then went up to 85.77 in cycle II. It can be concluded that the discovery learningoutcomes on thematic integrated learning.